If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2-(2x-7)+5=23
We move all terms to the left:
2-(2x-7)+5-(23)=0
We add all the numbers together, and all the variables
-(2x-7)-16=0
We get rid of parentheses
-2x+7-16=0
We add all the numbers together, and all the variables
-2x-9=0
We move all terms containing x to the left, all other terms to the right
-2x=9
x=9/-2
x=-4+1/2
| 3x+36=28 | | 3^(4-x)=81 | | X+0.1x=250 | | 2,1-1,2m= | | x^2+9x+1000=0 | | .x–4–4x=6x+9–8x | | 10-3y=y-2 | | 10=-10x+9x | | -16=-4x+6x | | 3x+2(x+2)=22-3(2x-1) | | 14x²-35x=0 | | 4x^2+6x+12=10 | | 9(7x-2)=5(10x-1) | | 2.34n+7=250 | | 23x-5+21x5=180 | | (4x-5)(3x+7)=3 | | (4x-5)(3x-7)=3 | | 5s^2+s+4=0 | | 2(3x+4)=5(2+x) | | حددخاصيةالمساواةالمستعملة3m+4=193m+4-4=19-4 | | 25x^2-9x-16=0 | | 5a+2(1,25-0,75a)=6 | | 7q÷8=14 | | 5a+2(1,5-0,75a)=6 | | 5/16=4/x | | 3x/4=–54 | | 2x2–98=0 | | 0=4x2+24x | | .6x-4=4x+10 | | 32x-16x^2-15=0 | | -18y+2y-45=0 | | 3+(4x)^-1/6=5 |